Analisis Miskonsepsi Siswa Kelas V Sekolah Dasar Pada Materi Konsep Keliling Bangun Datar - Nur Aina; Fajar . (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study aims to identify the misconceptions experienced by fifth-grade elementary school students in understanding the concept of perimeter of plane figures. The research was conducted because some students still had difficulties in understanding perimeter concepts, particularly in applying formulas and calculating the total length of sides. This study employed a descriptive quantitative method involving fifth-grade students from SD Negeri 3 Menteng and SD Negeri 1 Palangka. Data were collected through written tests consisting of questions related to the perimeter of squares, rectangles, and triangles. The data were analyzed based on the accuracy of students’ answers and the types of errors found in the problem-solving process. The results indicated that most students were able to answer the questions correctly. However, several misconceptions were still identified, including incorrect formula usage, calculation errors, and limited understanding of perimeter concepts. In addition, differences in students’ levels of understanding were found between the two schools.